Growth performance, carcass characteristics, meat quality and profitability of local Malawi goats under pen fattening conditions - Chilanga, F. (International Institute of Tropical Agriculture, 2020)
A study was conducted to evaluate the effect of feeding different fattening diets based on locally available non-conventional feed resources on growth performance, carcass characteristics, meat quality and profitability of local Malawi goats fattened under pen feeding. Fifty uncastrated local Malawi goat weaners (5 – 6 months old) with initial body weight of 11.55 ± 2.04kg were divided into five groups of 10 animals each and randomly allocated to five treatment categories as follows: S = 60% Rhodes grass (Chloris gayana) hay + 40% soya bean (Glycine max)-based concentrate; SA = 60% Rhodes grass (Chloris gayana) hay + 40% soya bean (Glycine max) and white thorn tree (Acacia polyacantha) leaf meal-based concentrate; B= 60% Rhodes grass hay (Chloris gayana) + 40% baobab (Adansonia digitata) seedcake-based concentrate; BA= 60% Rhodes grass hay (Chloris gayana) + 40% baobab (Adansonia digitata) seedcake and white thorn tree (Acacia polyacantha) leaf meal-based concentrate; and C = grazing only. Animals in S, SA, B and BA were under pen feeding with total confinement for the entire 84 days trial period while those in C were under extensive management. At the end of the feeding trial, goats were slaughtered for evaluation of carcass and meat quality. Pen fed goats on baobab only-based diet had significantly higher daily gains, final weights and total weight gain, and better feed conversion ratio than the rest of the treatments (P < 0.05). Grazing goats had the least daily gains, carcass weight, final weight and total weight gain. Lightness (L*) and yellowness (b*) of the meat was higher in goats under baobab-based pen feeding diets as compared to all other diets. Goat meat from the control diet was darker than that from the rest of diets (lowest L*). Estimated gross margins were high in grazing animals followed by baobab only-based pen feeding diet. However, baobab only-based pen feeding diet had the highest estimated net profit. Current findings indicate that pen feeding of local Malawi goats based on locally available non-conventional feed resources like baobab seedcake improves growth performance, carcass characteristics, meat quality, and profit.